Eruca sativa Mill. seed extract promotes anti‐obesity and hypoglycemic effects in mice fed with a high‐fat diet. (3rd November 2020) - Piragine, Eugenia; Flori, Lorenzo; Di Cesare Mannelli, Lorenzo; Ghelardini, Carla; Pagnotta, Eleonora; Matteo, Roberto; Lazzeri, Luca; Martelli, Alma; Miragliotta, Vincenzo; Pirone, Andrea; Testai, Lara; Calderone, Vincenzo
Abstract : Obesity is currently considered a major source of morbidity, with dramatic complications on health status and life expectancy. Several studies demonstrated the positive effects of Brassicaceae vegetables on obesity and related diseases, partially attributing these beneficial properties to glucosinolates and their derivatives isothiocyanates. Recently, isothiocyanates have been described as a hydrogen sulfide (H2 S)‐releasing moiety, suggesting that H2 S may be at least in part responsible for the beneficial effects of Brassicaceae . In this work, the metabolic effects of an extract obtained from Eruca sativa Mill. seeds (E.S., Brassicaceae ), containing high levels of glucoerucin, were evaluated in an experimental model of obesity. Male balb/c mice were fed for 10 weeks with standard (Std) diet or high fat (HF) diet supplemented with E.S. E.S. significantly contained the body weight gain in this obesity model, improving also glucose homeostasis. Interestingly, lower values of white adipose tissue mass and a significant reduction of adipocytes size were also observed. Moreover, E.S. enhanced the adipocytes metabolism, improving the citrate synthase activity and reduced triglyceride levels in mice fed with HF diet. Taken together, these results suggest that E.S. is endowed with an interesting translational and nutraceutical value in the prevention of metabolic disorders, suggesting that H2 S could be a key player.